Analysis of water parameters in experimental ponds of PRJSC “Khmelnytskrybhosp” as a prerequisite for the creation of replacement and brood stocks of Antoniny-Zozulenets carps (Cyprinus carpio Linnaeus, 1758) - V. Oborskyi; N. Mykhailenko; T. Bersan; H. Kurinenko; L. Drahan (Ribogospodarsʹka Nauka Ukraïni, 2025)
Purpose. To provide an assessment of the temperature and oxygen regimes, considering the main chemical parameters of water when creating replacement and brood stocks of Antoniny-Zozulenets carps grown in the conditions of PrJSC “Khmelnytskrybhosp”.